Analysis of Elementary School Students’ Difficulties in Speaking Skills in English Language Learning: A Literature Study - Tiarnita Maria Sarjani Br Siregar; Apriyanda; Husnah Siregar; Noven Christoper Butar Butar (Global Writing Academica Researching & Publishing, 2026)
This study aims to analyze the types of difficulties and causal factors experienced by elementary school students in speaking skills in English learning through a literature review. The method used is descriptive qualitative with data collection techniques in the form of reviews of various relevant journals and books. The results of the study indicate that speaking difficulties are complex and encompass both linguistic and non-linguistic aspects. From a linguistic perspective, the main obstacles include limited vocabulary, pronunciation errors due to differences in the sound systems of Indonesian and English, and a weak understanding of grammar in constructing simple sentences. Meanwhile, from a non-linguistic perspective, psychological factors such as shyness, fear of making mistakes, and low self-confidence inhibit students’ courage to speak. In addition, external factors such as limited opportunities for practice, less communicative learning methods, and an environment that does not support the use of English also exacerbate these difficulties.